Product and market development for subsistence marketplaces - Rosa, José Antonio, 1955-; Viswanathan, Madhu (Elsevier/JAI, 2007)
This volume provides a more detailed and profound understanding of an important and, until recently ignored, global phenomenon: marketplaces where individuals living in poverty buy/sell products and services. It is estimated that as many as 4 billion people with buying power exceeding $14 trillion fall into this market segment. Historically, the research in this area was conducted among consumers from industrialized economies. This research is rooted in fundamental assumptions about literacy and numeracy skills, life stability, cognitive predilections, and consumer access to basic resources such as education, water, and sanitation that often do not hold for poverty-stricken marketplaces.This volume presents a collection of articles that describe this particular group of consumers and entrepreneurs, and inform us on better ways to understand, reach, and empower them. The potential to do well by doing good in these impoverished marketplaces is very high, it is the hope of the editors that this reference will jumpstart the development of new theories, frameworks, and models that address both consumption and entrepreneurship in this particular market. This series publishes conceptual and empirical papers that deal with international topics from all areas within the management field. The organizations studied can be domestic or multinational, and the level of analysis can be macro or micro. Through new theoretical insights, managerial application, methodology, or data, the papers make a significant contribution to advancing knowledge about international management.
Includes selected conference papers.
Keywords: Consumer behavior -- Developing countries -- Congresses.; Consumers -- Developing countries -- Congresses.; Marketing -- Developing countries -- Congresses.; Subsistence economy -- Congresses.; elektronické knihy; electronic books